2014
DOI: 10.1007/s11999-014-3825-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Triangular Fibrocartilage Complex Abnormalities Regardless of Symptoms Rise With Age: Systematic Review and Pooled Analysis

Abstract: Background Triangular fibrocartilage complex abnormalities seem to be more common with age, but the degree to which this is so, and the degree to which the presence of an abnormality is associated with symptoms, are topics of controversy. Questions/purposes We wished to perform a systematic review to determine the prevalence of triangular fibrocartilage complex abnormalities, and to determine if the prevalence of abnormalities are greater with increasing age. In addition, we stratified age groups based on symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 27 publications
1
42
0
4
Order By: Relevance
“…Seventy percent of symptomatic patients and 38% of asymptomatic patients had TFCC injury in the age group 50–69 years. 1 In addition to wrist pain, TFCC injuries result in decreased grip strength and impaired hand function. 2 TFCC injuries are managed non-operatively initially.…”
mentioning
confidence: 99%
“…Seventy percent of symptomatic patients and 38% of asymptomatic patients had TFCC injury in the age group 50–69 years. 1 In addition to wrist pain, TFCC injuries result in decreased grip strength and impaired hand function. 2 TFCC injuries are managed non-operatively initially.…”
mentioning
confidence: 99%
“…These findings persuades that the occurrence of incidental fibrocartilage complex abnormalities commonly occur independent of the symptoms and probability of their prevalence increases with age. It is also not clear whether the interventions used for addressing triangular fibrocartilage complex variations are better as compared to the natural history because of varying surgical outcomes they provide [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Case presentation and brief overview of literature with regard to general, specific and practicable aspects to primary trauma-related surgical treatment including possible salvage options at the distal radioulnar joint Longstanding UPV is generally associated with secondary degenerative lesions of the triangular fibrocartilage due to it compression, and additionally, primary degenerative lesions of the triangular fibrocartilage with or without UPV and in the absence of any clinical symptoms are also well known but it mostly occur in elderly patients aged 60 years and older [43][44][45][46][47]. Hence, it cannot always be concluded that a lesion of the triangular cartilage, assessed by MRI and wrist arthroscopy, in a young patient with evident acute traumatic UPV in which the triangular cartilage is generally detached or disrupted could mainly be caused by a pre-existing non-traumatic degenerative lesion, or that a chronic ulnar-sided wrist pain in an elderly patient with evident longstanding UPV longer than 2 mm (Figures 4 and 5) is based on a lesion of the triangular cartilage that consequently would requires MRI and wrist arthroscopy.…”
Section: Discussionmentioning
confidence: 99%